Peningkatan Hasil Belajar Pada Materi Indahnya Keberagaman Di Negeriku Kelas IV SD Menggunakan Model Pembelajaran Kooperatif Tipe Snowball Throwing - Suci Wulandari; Wiwik Lestari; Nora Alisa Pulungan (Journal on Education, 2024)
This research aims to determine learning outcomes on the material Cultural Diversity of My Nation using the Snowball Throwing learning model. This research is Classroom Action Research (PTK). This research was conducted in two cycles and each cycle consisted of 4 stages, namely planning, implementation, observation and reflection. From the research results, classical student learning activities have increased. In the pre-cycle, the average learning outcome was 8 people (30.77%) and 18 people (69.23%) incomplete. In cycle I, the average learning outcome was 16 people (61.54%) and 10 people (38.46%) incomplete. In cycle II, the average learning outcomes of 24 students (92.31%) were completed and 2 students were incomplete (7.69%). The conclusion from the results of this research shows that by using the Snowball Throwing learning model student learning outcomes increased significantly in the material Cultural Diversity of My Nation in Class IV SDN 106181 Sukamandi Hilir.